Silicon Valley Bank crisis and banking and technology sector: evidence from Israel - Ow, Hao Chen (2024)
This study investigates the impact of SVB crisis on the banking and technology sectors of Israel. There are many research papers that have investigated the impact of SVB crisis on the global equity markets. However, there is none that has done a sectoral analysis on the countries that are impacted by the collapse of SVB. By using event study methodology, the results of this paper have shown that the banking sector is negatively impacted at the beginning of the collapse of the SVB but turns to positively impacted after few days of the collapse of the SVB and the technology sector is positively impacted from the collapse of SVB. The results also proved that financial contagion is present and the banking and technology sector of Israel are not efficient during the SVB crisis. Furthermore, the results prove that the impact of SVB crisis is different for both the banking and technology sectors of Israel. This paper purposed that investors should short sell or not include the banking stocks in the portfolio for the first two days after the collapse of SVB and should include the banking stocks in the portfolio starting from the third day after SVB has collapse to increase expected returns of the portfolio. Besides that, the results suggest that investors should invest more in the technology sector after the collapse of SVB compared to the period before the collapse of SVB.